2011
DOI: 10.21829/azm.2011.271736
|View full text |Cite
|
Sign up to set email alerts
|

Morfometría geométrica y filogenia en Rhodniini (Hemiptera, Reduviidae) de Venezuela

Abstract: . 2011. Morfometría geométrica y filogenia en Rhodniini (Hemiptera, Reduviidae) de Venezuela. Acta Zool. Mex. (n. s.), 27(1): 87-102. RESUMEN. La tribu Rhodniini incluye los géneros Rhodnius Stål y Psammolestes Bergroth. Evidencias enzimática y molecular sugieren la monofilia de la tribu. La mayoría de las especies son selváticas encontrándose en palmas y en nidos de aves. Tradicionalmente ambos géneros fueron considerados grupos relacionados; no obstante, estudios moleculares cuestionan la monofilia de Rhodni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 47 publications
1
9
0
7
Order By: Relevance
“…Combined studies of morphometric and molecular data to answer phylogenetic hypothesis has been found to be highly consistent and in agreement (Caumul & Polly, 2005;Clouse et al, 2009;Giribet et al, 2012), indicating that the morphometric data contain significant phylogenetic information. Moreover, it has been found that phylogenetic analyses based solely on morphometric data can produce strong hypotheses (Guerrero et al, 2003;González-José et al, 2008;de Bivor et al, 2010;Soto-Vivas et al, 2011). The results show a strong agreement with previous molecular results.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Combined studies of morphometric and molecular data to answer phylogenetic hypothesis has been found to be highly consistent and in agreement (Caumul & Polly, 2005;Clouse et al, 2009;Giribet et al, 2012), indicating that the morphometric data contain significant phylogenetic information. Moreover, it has been found that phylogenetic analyses based solely on morphometric data can produce strong hypotheses (Guerrero et al, 2003;González-José et al, 2008;de Bivor et al, 2010;Soto-Vivas et al, 2011). The results show a strong agreement with previous molecular results.…”
Section: Discussionsupporting
confidence: 81%
“…Coordinates x and y were analyzed directly with new algorithms for landmark data developed by Catalano et al (2010). A combination of ratchet, sectorial search, tree drifting, and tree fusing search algorithms was used for the selection of optimal trees and for the estimation of Jackknife values as a measure of support (Farris et al, 1996;Aguilar-Medrano et al, 2011;Soto-Vivas et al, 2011). Finally, morphological variables {x, y coordinates) were optimized on to the phylogeny.…”
Section: Phylogenetic Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…En otros casos, las diferencias en la conformación podrían ser consecuencia de interacciones más complejas, que contenienen así información que permitiría postular hipótesis filogenéticas (Soto-Vivas et al 2011).…”
Section: Discussionunclassified
“…Esta técnica se ha utilizado en diversas clases de organismos vegetales y animales (vertebrados e invertebrados), y particularmente en insectos de importancia médica, como triatóminos (Triatominae), flebótomos (Phlebotominae) y mosquitos (Culicidae). Ha sido empleada en estudios de estructura poblacional , Belen et al 2004, Schachter-Broide et al 2004, Dvorak et al 2006, Soto-Vivas et al 2007, identificación de especies (Matías et al 2001, Villegas et al 2002, Calle et al 2008, para detectar diferencias entre parentales de campo y descendientes de laboratorio (Jaramillo & Wolff 2002), así como en estudios filogenéticos (Soto-Vivas et al 2011).…”
unclassified